Clearance of Thrombin from Circulation in Rabbits by High-affinity Binding Sites on Endothelium: POSSIBLE ROLE IN THE INACTIVATION OF THROMBIN BY ANTITHROMBIN III - Lollar, Pete (1980)
The clearance of (125)I-thrombin and diisopropylphosphoryl-(125)I-thrombin (DIP-thrombin) from the circulation in rabbits was studied. When given either intraarterially or intravenously, DIP-thrombin, which is active-site blocked, was ∼90% cleared from the circulation by 1 min, the time of earliest sampling, indicating a large first-pass effect. DIP-thrombin given intravenously is found predominantly in the lungs, whereas DIP-thrombin injected into the aortic arch is distributed diffusely in approximate proportion to the blood supply. Renal artery, femoral artery, ear artery, left atrium, and portal vein infusions demonstrate that kidney, muscle, ear, heart, and liver, respectively, can remove DIP-thrombin from the circulation. These data imply that the clearance of DIP-thrombin is not a function of a specific organ but of the vascular bed per se. The clearance of DIP-thrombin was reversible since injection of 0.5 mg of unlabeled DIP-thrombin 10 min after the injection of a tracer dose of DIP-(125)I-thrombin resulted in the rapid reappearance of the DIP-(125)I-thrombin into the circulation. In addition, the clearance of DIP-thrombin was saturable, i.e., clearance of DIP-(125)I-thrombin was inhibited by unlabeled DIP-thrombin in a dose-dependent fashion. In vivo Scatchard analysis of the saturation of the clearance process demonstrated that DIP-thrombin can be removed by binding to high-affinity binding sites, since dissociation constants (K(D)) of 10 and 13 nM were obtained for human and bovine DIP-thrombin, respectively. In contrast to DIP-thrombin, ∼75% of the radioactivity associated with active thrombin remained in the circulation at 1 min. By 10 min 55% of (125)I-thrombin had been removed from the circulation, and essentially all of the radioactivity can be accounted for in the liver. Sodium dodecyl sulfate-polyacrylamide gel radioelectrophoresis of plasma samples taken after injection of (125)I-thrombin demonstrated that all of the active thrombin was converted to covalent thrombin-antithrombin III complex by the time of initial sampling (30 s). The in vitro conversion of (125)I-thrombin to thrombin-antithrombin III complex was considerably slower (50±5% conversion at 30 s). The simultaneous injection of excess unlabeled DIP-thrombin inhibited the rate of formation of (125)I-thrombin-antithrombin III complex formation in vivo (but not in vitro), which suggests that the binding of active thrombin to the high affinity binding sites is required for the rapid inactivation of thrombin in vivo. We propose that (a) thrombin in the circulation binds to active site-independent high-affinity binding sites on the endothelial cell surface; (b) the inactivation of thrombin by antithrombin III is faster in vivo than in vitro because the high-affinity binding sites, present in a high concentration in the microcirculation, catalyze the reaction; (c) thrombin-antithrombin III complexes are selectively removed by the liver.